General Opial type inequality - Barbir, Ana; Himmelreich, Kristina Krulić; Pečarić, Josip (Aequationes mathematicae, 2015)
In this paper our goal is to give a general Opial type inequality. We consider two functions, convex and concave and prove a new general inequality on a measure space (Ω,Σ, μ ). The obtained inequalities are not direct generalizations of the Opial inequality but are of Opial type because the integrals contain a function and its integral representation. We apply our result to numerous symmetric functions and obtain new results that involve Green’s functions, Lidstone series and the Hermite’s interpolating polynomials.